Plant communities and food webs - Dobson, Andy; Hutchinson, Matthew C.; Batterman, Sarah (Frontiers in Ecology and Evolution, 2023)
Recent theoretical work has provided major new insights into the ways that species interactions in food webs are organized in ways that permit the coexistence of significant numbers of species. But, we seem to have forgotten about trees, shrubs and grasses that are the basal species in all terrestrial ecosystems. Many of the food webs available for analysis over the last 30 years were based on freshwater or marine systems where algae were the main plants. Trees are very different from algae; they can live for centuries, while annually producing leaves, fruits and seeds that provide nutrients for a diversity of species on higher trophic levels. In sharp contrast to algae, they are only partly consumed by herbivores and usually compensate or recover from herbivory. Moreover, each individual tree supports its own food web of species that are only partially coupled to those of surrounding trees. If we are going to apply our theoretical understanding of food-web structure to species-rich terrestrial ecosystems in ways that are insightful for conservation, then we need a deeper examination of the role that higher plants play in food webs. In this article, we make a plea to more sharply consider higher plants in food webs and to do this by combining recent theoretical work on food webs, with recent empirical and theoretical work on plant communities. Ultimately, we argue for a deeper integration of plant community ecology into studies of food webs.